Optical recording of light-evoked calcium signals in the functionally intact retina - Denk, Winfried (The National Academy of Sciences, 1999)
Using two-photon excitation of fluorescent indicator dyes, we measured calcium concentration transients in retinal ganglion and amacrine cells without destroying the light sensitivity of the retina by maximally activating or bleaching the photoreceptors. This allowed an immediate assessment of the cellular morphology and study of the calcium signals evoked by visual stimuli. Calcium dynamics in individual dendritic processes could be examined for extensive periods without deterioration and with little apparent phototoxicity at excitation wavelengths of from 930 to 990 nm. Light-evoked increases in calcium were resolved in ganglion- and amacrine-cell neurites, making it possible to use optical recording to study the relationship between calcium signaling and retinal function.